Pengaruh Kepemimpinan dan Pengawasan Terhadap Disiplin Kerja Pegawai Pada Dinas Pariwisata dan Kebudayaan Kota Bima - Sugeng Aryanto; Jaenab Jaenab (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This research aims to determine the influence of leadership and supervision on employee work discipline at the Bima City Tourism and Culture Office. The sampling technique used in this research used a proportional sampling type, totaling 43 ASN employees of the Public Works and Spatial Planning Department of Bima Regency. Data collection techniques were observation, questionnaires, literature study, while data analysis techniques were validity tests, reliability tests, assumption tests. classical, multiple linear regression analysis, Correlation Coefficient, Coefficient of Determination, t test, F test. The results of the research show that the Leadership variable (X1) has a significant influence on work discipline (Y) as evidenced by the correlation coefficient of the leadership variable (X1) with the test value calculated r is 0.752 > r table 0.300, while the Supervision variable (X2) has a calculated r of 0.752, which is a value greater than r table 0.300. This proves that there is a significant influence between supervision (X2) on Work Discipline (y). Based on the f test, it shows that the probability value is <0.005, so it can be said that there is a joint significant influence between the independent variable and the dependent variable. This means that there is a positive influence between leadership (X1) and supervision (X2) on work discipline (Y). The research conclusion is based on calculations that there is a significant influence between leadership and supervision on work discipline. Based on the results of the analysis, it can be concluded that together leadership and supervision have a significant positive influence on work discipline at the Bima City Tourism and Culture Office.